Clinical predictors of driving simulator performance in drivers with multiple sclerosis. (November 2021) - Krasniuk, Sarah; Classen, Sherrilene; Morrow, Sarah A; Alvarez, Liliana; He, Wenqing; Srinivasan, Sivaramakrishnan; Monahan, Miriam
Background: Drivers with multiple sclerosis (MS) may experience visual–cognitive impairment that affects their fitness to drive. Due to limitations associated with the on-road assessment, an alternative assessment that measures driving performance is warranted. Whether clinical indicators of on-road outcomes can also predict driving performance outcomes on a driving simulator are not fully understood. Objective: This study examined if deficits in immediate verbal/auditory recall (California Verbal Learning Test–Second Edition; CVLT2-IR) and/or slower divided attention (Useful Field of View™; UFOV2) predicted deficits in operational, tactical, or strategic maneuvers assessed on a driving simulator, in drivers with and without MS. Methods: Participants completed the CVLT2-IR, UFOV2, and a driving simulator assessment of operational, tactical, and strategic maneuvers. Results: Deficits in immediate verbal/auditory recall and slower divided attention predicted adjustment to stimuli errors, pertaining to tactical maneuvers only, in 36 drivers with MS (vs 20 drivers without MS; F (3, 51) = 6.1, p  = 0.001, R 2  = 0.3, R a d j 2 = 0 . 2 ). Conclusion: The CVLT2-IR and UFOV2 capture the visual and verbal/auditory recall, processing speed, and divided attention required to appropriately adjust to stimuli in a simulated driving environment. Clinicians may use the CVLT2-IR and UFOV2 as precursors to driving performance deficits in drivers with MS.